Analysis of Sangihe Islands Movements derived from Recent GPS Observation - Krishna Fitranto Nugroho; Leni Sophia Heliani (Jurnal Geospasial Indonesia, 2019)
Sangihe Islands is one of the districts located in the border region of the Republic of Indonesia precisely located in North Sulawesi Province which borders with the Philippines. Sangihe subduction zone is a subduction between the Sangihe plate and the Maluku sea plate. (Di Leo, et al., 2012). This situation causes the Sangihe Islands region to be very prone to earthquake and others disasters, so mitigation efforts are needed to minimize casualties and losses in other material forms. One of these efforts is mapping the potential of earthquakes through Geodynamic studies which are represented at the point of deformation control. This study is using four times GNSS observations epoch 2015, 2016, 2017 and 2018 tied to ITRF 2014. The data used for 3D deformation analysis with the multiepoch method to calculate the movement speed of the Sangihe plate and simultaneous tectonic plate strain observation. The results of this study are the coordinates and accuracy values of monitoring point also the plate movement speed and annual tectonic plate strain values. The movement speed of the Sangihe plate is SGH1 point is having horizontal deformation of 9.88 mm / year to the southeast and vertical deformation descend by 58.66 mm/year. SGH3 point is having horizontal deformation of 12.74 mm/year to the southeast and vertical deformation descend by 18.51 mm/year. SGH4 point is having horizontal deformation of 19.04 mm/year to the southeast and vertical deformation descend by 5.27 mm/ year. This research also proves the hypothesis of a change in the volume of the Sangihe Islands tectonic plate based on the values of normal strain parameters and shear strain in the fraction of 10-6 to 10-4 strains.